The NB‐LRR proteins RGA4 and RGA5 interact functionally and physically to confer disease resistance. (14th July 2014) - Césari, Stella; Kanzaki, Hiroyuki; Fujiwara, Tadashi; Bernoux, Maud; Chalvon, Véronique; Kawano, Yoji; Shimamoto, Ko; Dodds, Peter; Terauchi, Ryohei; Kroj, Thomas
Abstract Plant resistance proteins of the class of nucleotide‐binding and leucine‐rich repeat domain proteins (NB‐LRRs) are immune sensors which recognize pathogen‐derived molecules termed avirulence (AVR) proteins. We show that RGA4 and RGA5, two NB‐LRRs from rice, interact functionally and physically to mediate resistance to the fungal pathogen Magnaporthe oryzae and accomplish different functions in AVR recognition. RGA4 triggers an AVR‐independent cell death that is repressed in the presence of RGA5 in both rice protoplasts and Nicotiana benthamiana. Upon recognition of the pathogen effector AVR‐Pia by direct binding to RGA5, repression is relieved and cell death occurs. RGA4 and RGA5 form homo‐ and hetero‐complexes and interact through their coiled‐coil domains. Localization studies in rice protoplast suggest that RGA4 and RGA5 localize to the cytosol. Upon recognition of AVR‐Pia, neither RGA4 nor RGA5 is re‐localized to the nucleus. These results establish a model for the interaction of hetero‐pairs of NB‐LRRs in plants: RGA4 mediates cell death activation, while RGA5 acts as a repressor of RGA4 and as an AVR receptor.